Economics for Policy: Expanding the Boundaries Essays by Peter Gorringe Edited by A Jones, R Procter and G Scobie - Palmer, Matthew SR (Victoria University of Wellington Law Review, 2001)
Arthur Grimes, Alan Jones, Roger Procter and Grant Scobie (eds) Economics for Policy: Expanding the Boundaries, Essays by Peter Gorringe (Institute of Policy Studies, Wellington, 2001) 265 pages. This article is a book review of Economics for Policy, a collection of economic policy essays written by Peter Gorringe. According to Palmer, the collection of essays outline Gorringe's use of new institutional economics transcended many limits of conventional economic analysis. Palmer also argues that Gorringe always re-examined conclusions through the principles of open and honest intellectual inquiry.